The modern information systems for controlling the railway traffic as an indispensable tool of an infrastructure manager - Mestický, Štefan; Krásenský, David (Univerzita Pardubice, 2010)
The information systems of an infrastructure manager (IM) are today an indispensable part of its basic technological processes. Their significance has been growing even more in the setting of the liberalized transport market, where many private railway undertakings (RU) or operators enter the railway network and content for its spare capacity. The contribution discusses covers the high-level structure of the key information systems of the infrastructure manager, their coverage of the aforementioned technological processes, from designing the timetables and ordering ad hoc paths, to the operational control in all of its spatial and time levels, to assessing the traffic and resolving the exceptional situations. As the most important feature, the authors emphasize a profound integration of all these systems, which involves unifying all the databases and facilitates reusing the captured data, which boosts the overall efficiency of the system. The authors draw from their huge experiences of developing, solving, implementing, and operating these systems, above all in the environment of Czech and Slovak railway networks.
Keywords: railway transport; infrastructure manager; traffic control; information systems; integrated solution; information interoperability; mission-critical systems; planning